2017
DOI: 10.1038/ncomms15866
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of EGFR signalling by the human folliculin tumour suppressor protein

Abstract: Germline mutations in the Folliculin (FLCN) tumour suppressor gene result in fibrofolliculomas, lung cysts and renal cancers, but the precise mechanisms of tumour suppression by FLCN remain elusive. Here we identify Rab7A, a small GTPase important for endocytic trafficking, as a novel FLCN interacting protein and demonstrate that FLCN acts as a Rab7A GTPase-activating protein. FLCN−/− cells display slower trafficking of epidermal growth factor receptors (EGFR) from early to late endosomes and enhanced activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 67 publications
(117 reference statements)
2
46
0
1
Order By: Relevance
“…This led to the hypothesis that FLCN binds Rab GTPases and regulates vesicular trafficking processes (Nookala et al, 2012). In support of this view, three recent reports have shown that FLCN interacts through its DENN domain with Rab34, Rab7A and Rab35 (Starling et al, 2016;Laviolette et al, 2017;Zheng et al, 2017). In one study, Dodding's group discovered that the FLCN-Rab34 interaction regulates the intracellular movement of lysosomes in a nutrient-sensitive manner in HeLa cells (Starling et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This led to the hypothesis that FLCN binds Rab GTPases and regulates vesicular trafficking processes (Nookala et al, 2012). In support of this view, three recent reports have shown that FLCN interacts through its DENN domain with Rab34, Rab7A and Rab35 (Starling et al, 2016;Laviolette et al, 2017;Zheng et al, 2017). In one study, Dodding's group discovered that the FLCN-Rab34 interaction regulates the intracellular movement of lysosomes in a nutrient-sensitive manner in HeLa cells (Starling et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…recently been found to interact with Rab7A in several human tumor cell lines (Laviolette et al, 2017), we considered the FLCN-Rab7A interaction as a positive control in our co-IP experiments. It is probably worth noting that, on the basis of these co-IP data; it seems that only a small proportion of GFP-tagged Rab proteins coimmunoprecipitated with FLCN.…”
Section: Flcn Interacts With Rab11a Through Its Denn Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of FLCN‐FNIPs interaction drives upregulated mTORC1‐dependent protein synthesis, upregulated PGC1 α ‐ dependent mitochondrial oxidative metabolism and aberrant kidney cell proliferation . Crystallography of FLCN protein exhibited that FLCN has a DENN domain in its C‐terminus, suggesting FLCN may act as a modifier for Rab small GTPase family as well as a regulator for membranous trafficking . In addition, FLCN shows either GAP activity towards RagC/D GTPases or GEF activity towards RagA/B GTPases, which consequently regulates mTORC1 localization on lysosomes, implying that FLCN may regulate multiple small GTPases .…”
Section: Birt‐hogg‐dubé’ (Bhd) Syndromementioning
confidence: 99%
“…[20][21][22][23][24] Crystallography of FLCN protein exhibited that FLCN has a DENN domain in its C-terminus, suggesting FLCN may act as a modifier for Rab small GTPase family as well as a regulator for membranous trafficking. 25,26 In addition, FLCN shows either GAP activity towards RagC/D GTPases or GEF activity towards RagA/B GTPases, which consequently regulates mTORC1 localization on lysosomes, implying that FLCN may regulate multiple small GTPases. 27,28 These findings highlight that FLCN plays important roles in metabolism, and disruption of metabolism under FLCN deficiency may drive aberrant kidney cell proliferation.…”
mentioning
confidence: 99%